DIMENSI KEISLAMAN MASYARAKAT BANTEN PADA PRAKTIK TAREKAT QADIRIYAH NAQSYABANDIYAH - Abdullah, Wawan; Ma'mur, Ilzamudin; Gunawan, Agus; Syam, Ahmad Bazari (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
The study of the Qadiriyah congregation in Banten needs to be explored and known through study and research. This research uses a qualitative method with a library study approach, data collection techniques through books, journals, magazines, reports and written sources that are relevant to the research. The research results show that: 1) suluk is the initial process of knowing God. 2) dhikr which is strengthened in qadariyah chanting is the reading of monotheism sentences in different ways taught by the teacher. 3) read prayers; The Qadiriyah Order uses "Ibadallah Rijalallah", 4) fasting is a unique fast carried out by students on the teacher's orders. 5) manaqiban, namely reading texts related to loyalty to the good morals of Sheikh Abdul Qadir al-Jailani. 6) hataman, a routine activity carried out by the qadiriyah congregation together. The implication of the research is that the practice of the Qadiriyah Tarekat has become a tradition of the Banten people and has become rooted in a culture that cannot be abandoned. The implications of this research activity are: 1) strengthening local Islamic identity, 2) developing religious education, 3) deep understanding of plurality, 4) promoting development and training programs, 5) contributing to community development, 6) strengthening collaboration networks with other parties. related, 7) development of educational literature. These implications can be used as a basic perspective in designing and making decisions.